2023
DOI: 10.54150/alirsyad.v2i1.116
|View full text |Cite
|
Sign up to set email alerts
|

Implementasi Regulasi Keuangan Berkelanjutan Pada Bank Syariah dan Bank Konvensional di Indonesia

Abstract: This article describes the implementation of sustainable financial policies by Islamic Banks and Conventional Banks in supporting environmentally sound business activities in their business activities to minimize environmental damage. The research method in this study is the normative juridical method, namely descriptive-analytical. This research concludes that after the publication of the sustainable finance policy, the business activities of financial service institutions are still in the stage of raising aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…There are several studies that have focused on exploring the evolution of green banking and sustainable finance, as well as identifying prospective research topics and areas for further study (Agustia et al, 2021;Andatu & Hilabi, 2023;Cahyaningtyas et al, 2023;Darma, 2022;Dewi & Sudarsono, 2021;Djajadiwangsa & Alversia, 2022;Gumantiny, 2022;Hayati et al, 2020;Kumajas et al, 2022;Malau & Rambe, 2022;Migliorelli, 2021;Yulia Nur Atriksa & Murwaningsari, 2022). In addition, researchers have examined investments in green banking, including green bonds, green insurance, and weather derivatives, while highlighting the determinants of green finance and the role of sustainable financial technology (Andatu & Hilabi, 2023). Furthermore, a review of existing literature on green banking has identified important themes such as strategies to improve green banking, efforts to make green investments profitable, and challenges in green banking (Cahyaningtyas et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that have focused on exploring the evolution of green banking and sustainable finance, as well as identifying prospective research topics and areas for further study (Agustia et al, 2021;Andatu & Hilabi, 2023;Cahyaningtyas et al, 2023;Darma, 2022;Dewi & Sudarsono, 2021;Djajadiwangsa & Alversia, 2022;Gumantiny, 2022;Hayati et al, 2020;Kumajas et al, 2022;Malau & Rambe, 2022;Migliorelli, 2021;Yulia Nur Atriksa & Murwaningsari, 2022). In addition, researchers have examined investments in green banking, including green bonds, green insurance, and weather derivatives, while highlighting the determinants of green finance and the role of sustainable financial technology (Andatu & Hilabi, 2023). Furthermore, a review of existing literature on green banking has identified important themes such as strategies to improve green banking, efforts to make green investments profitable, and challenges in green banking (Cahyaningtyas et al, 2023).…”
Section: Introductionmentioning
confidence: 99%